Relationship Between Child Phbs Behavior With Enterobiasis In Rt. 09/07 Susukan Village, East Jakarta - Salsabella Malsyah; Ndaru Andri Damayanti; Muhammadd Arsyad (Junior Medical Journal, 2022)
Enterobius vermicularis known as pinworms is an intestinal parasite that is disturbing and is still a public health problem worldwide, especially in children aged 6-10 years. Migration of female worms in the perianal area, especially at night, can disrupt children's sleep hours, and affect health in general. This study aims to see the correlation of clean and healthy lifestyle behavior (PHBS) in children with the presence of E. vermicularis in pre-school and elementary school age children. The method used is quantitative with a cross sectional approach. Examination results of 59 anal swab samples, one of which was positive for enterobiasis (1.7%). Filling in the child's PHBS behavior questionnaire, obtained from parental information and researchers' observations. Enteribiasis positive samples were found in pre-school children with poor PHBS behavior. Statistical tests showed that there was a significant correlation (p 0.05) in the incidence of enterobiasis with poor PHBS behavior in children.